Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria (Forest Ecology and Management, 2013)
The current trend of declining epiphytic richness caused by human activities (forest fragmentation, log- ging, agriculture, and livestock grazing) and the greater efforts required to sample and identify the most inconspicuous species have necessitated the use of indicators of the species richness. In this study, we examined the potential of predicting epiphytic lichen richness based on the richness of a single taxon (fam- ily) of the most conspicuous lichens (macrolichens) in Mediterranean woodlands. Since our working hypothesis is that the richness of some conspicuous elements is tightly connected with the total richness, we expect this connection is maintained even after composition shifts (for instance composition changes between coniferous and oak forests). In order to control the large set of confounding factors at macro- and microclimate scales our present study was conducted in 504 forest stands, which represented awide range of Mediterranean climates, management intensity levels, canopy cover types, and tree sizes. The presence/ absence of epiphytic lichens were determined in 7560 trees, which were dominated by coniferous (Pinus nigra and P. sylvestris) and oak (Quercus ilex ssp. ballota, Q. faginea, and Q. pyrenaica) species. In oak forests, the increased richness of Collemataceae and the complex known as ‘‘rest of Peltigerales’’ was followed by an increase in the overall epiphytic richness, whereas there was a strong positive correlation between Par- meliaceae and total epiphytic richness in coniferous forests. In both cases, the richness of these predictors increased in well-preserved forest stands with dense canopies. Thus, we propose the potential use of Par- meliaceae (for coniferous forests) and the Collemataceae and the ‘‘rest of Peltigerales’’ (for oak forests) as indicators in the Mediterranean region because they have a cosmopolitan distribution, grow in a wide range of environmental conditions, and are correlated with changes in the epiphytic richness caused by for- est disturbances. ?
From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )
Keywords: epiphytic lichens; Forest structure; Indicator species; Mediterranean; Species richness

Structure of ground-foraging ant assemblages in relation to land-use change in the northwestern Mediterranean region - Gómez, C; Casellas, D; Oliveras, J; Bas, J M (Biodiversity and Conservation, 2003)
The abandonment by humans of marginal and less productive zones signiﬁes an important change in land use in North Mediterranean agroecosystems. Human perturbations have led to a highly diversiﬁed landscape, with a mosaic made up of patches of land at different stages of succession, from cultivated ﬁelds to closed forest. Our aim here is to characterize ant assemblages and their functional groups in response to these land-use changes. This progressive abandonment results in an initial increase in ant richness and abundance, which can reach high levels if the succession proceeds as far as woodland. In terms of the ant functional groups, this land-use change implies: (1) the appearance of Subordinate Camponotini; (2) an increase in Generalized Myrmicinae, Cryptics and Cold-climate specialists in terms of ant species richness, overall abundance and, for Generalized Myrmicinae and Cryptics, an increase in abundance percentage; (3) a decrease in percentage abundance of Opportunists; (4) a progressive decrease in species richness as well as overall and percentage abundance of Hot-climate Specialists throughout the transformation from crops to woodlands; and (5) an initial increase of Dominant Dolichoderinae followed by a decrease in ant species richness, overall abundance and percentage abundance. Using the ant functional group approach for the clearly separate stages of the regeneration process is a promising method for comparing responses of ant communities to human land use.
Keywords: Ants; Functional groups; Indicator species; Land-use change; Mediterranean Region